(untitled) (Hematology Meeting Reports, 2009)
Desmopressin is an important hemostatic agent for patients with von Willebrand disease. It stimulates endogenous hemostasis by releasing von Willebrand factor (VWF) and coagulation factor VIII (FVIII) from storage sites. Most patients with the most prevalent subtype, type 1, respond well with sufficient increases of factor levels and shortening of the bleeding time. The post desmopressin levels of VWF and FVIII are dependent on the basal levels, and may be insufficient if basal levels are very low. In patients with type 2 VWD, desmopressin is usually not effective as the VWF is functionally defective. A recent European multicenter study investigated the effect of desmopressin in patients with severe type 1 and 2 and showed that only a minority of patients with VWF activity < 0.10 kIU/L or FVIII activity < 0.20 kIU/L or bleeding time >15 minutes responded sufficiently. Therefore it is important to test the effect of desmopressin in such patients before clinical use. Desmopressin is also a potent antidiuretic. There is a concern for side effects as it is used in 10-20 times higher doses than those used for antidiuretic purposes. Despite the larger doses, the magnitude of the antidiuretic effect is the same, indicating that this effect reaches a plateau already at low dosage levels. The duration of the antidiuretic effect after single hemostatic doses is about 24 hours. If treatment is prolonged with repeated doses, factor levels as well as serum sodium should be monitored and fluid intake restricted.